Adhesive sheet and laminate

The adhesive sheet with a (meth)acrylic polymer and silane coupling agent composition addresses peeling issues in adherends with different expansion and contraction rates, ensuring adhesion under temperature changes and high-temperature environments, particularly in automobile sunroofs and large building windows.

JP2025008400AActive Publication Date: 2025-01-20OJI HLDG CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023110554
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-05
Publication Date
2025-01-20
Estimated Expiration
2043-07-05

AI Technical Summary

Technical Problem

Conventional adhesive sheets fail to prevent peeling between adherends with different expansion and contraction rates under temperature changes or high-temperature environments, particularly in larger applications such as automobile sunroofs and large building windows.

Method used

An adhesive sheet with a specific adhesive layer composition containing a (meth)acrylic polymer and a silane coupling agent, having a gel fraction of 80% or more and residual stress of 3.0 kPa to 10.0 kPa after 60 seconds, adhering to the formula |(X1-X2)|≧0.1%, where X1 and X2 are the expansion/contraction rates of the adherends.

Benefits of technology

The adhesive sheet effectively prevents peeling between adherends with different expansion and contraction rates, maintaining adhesion under temperature changes and high-temperature environments, suitable for applications like automobile sunroofs and large building windows.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025008400000001
    Figure 2025008400000001
Patent Text Reader

Abstract

To provide an adhesive sheet which is used for laminating adherends having different rates of expansion and contraction and does not easily peel off from the adherends even in either a temperature change environment or a high-temperature environment.SOLUTION: There is provided an adhesive sheet which is used for laminating adherends having different rates of expansion and contraction and comprises an adhesive layer obtained from an adhesive composition, wherein the adhesive composition contains at least a main agent containing a (meth) acrylic polymer and a silane coupling agent, the gel fraction of the adhesive layer is 80% or more and the adhesive layer has a residual stress of 3.0 kPa or more to 10.0 kPa or less after 60 seconds after applying 15% torsional shear stress at 105°C.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a pressure-sensitive adhesive sheet and a laminate. [Background technology]

[0002] In recent years, adhesive sheets are materials formed having an adhesive layer mainly composed of, for example, an acrylic polymer, and are used for bonding various optical components such as touch panels and liquid crystal displays (LCDs), as well as for automobile sunroofs and large building windows.

[0003] Such adhesive sheets have been widely studied, and various means for improving not only adhesive strength but also various other performances have been proposed. For example, Patent Document 1 proposes an adhesive sheet with a release liner, which includes an adhesive sheet having a substrate and an adhesive layer, and a release liner disposed on the adhesive layer, and is said to be capable of easily releasing air and providing good adhesion when applied to an adherend during use.

[0004] On the other hand, a pair of adherends having different linear expansion coefficients (expansion and contraction coefficients) may be bonded together using a pressure-sensitive adhesive sheet. For example, a laminate in which a glass substrate and a resin substrate are bonded together with a pressure-sensitive adhesive sheet is known. It is also known that such a laminate can be applied to various applications such as sunroofs for automobiles and large windows for buildings. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2011-094057 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, a laminate in which adherends with different expansion and contraction rates are bonded together with a conventional pressure-sensitive adhesive sheet has a problem that, for example, peeling occurs at the end of the adherend due to the difference in the expansion and contraction rates between the adherends in an environment where temperature changes or high temperatures occur. This problem becomes more pronounced as the adherend becomes larger, and for example, the thicker the adherend is, the more likely it is to peel off in an environment where temperature changes or high temperatures occur. From this perspective, there has been a demand for a pressure-sensitive adhesive sheet that is less likely to peel off when adherends with different expansion and contraction rates are bonded together, even when placed in an environment where temperature changes or high temperatures occur.

[0007] The present invention has been made in consideration of the above, and aims to provide an adhesive sheet that, when adherends with different expansion and contraction rates are bonded together, is less likely to peel from the adherend, both in an environment where temperature changes occur and in a high-temperature environment. [Means for solving the problem]

[0008] Means for Solving the Problems The present inventors have conducted extensive research to achieve the above object, and as a result have found that the above object can be achieved by using a pressure-sensitive adhesive layer having specific physical properties, thereby completing the present invention.

[0009] That is, the present invention includes, for example, the subject matter described in the following sections. Item 1 A pressure-sensitive adhesive sheet used to bond a pair of adherends having different stretch rates, A pressure-sensitive adhesive layer is provided from the pressure-sensitive adhesive composition, The pressure-sensitive adhesive composition contains at least a base agent containing a (meth)acrylic polymer and a silane coupling agent, The pressure-sensitive adhesive layer has a gel fraction of 80% or more, the pressure-sensitive adhesive layer has a residual stress of 3.0 kPa or more and 10.0 kPa or less 60 seconds after application of a 15% torsional shear stress at 105°C, The following formula (1) |(X1-X2)|≧0.1% (1) (Here, when one of the pair of adherends is adherend A and the other is adherend B, X1 is the expansion / contraction rate (%) when adherend A is heated from 23°C to 110°C, and X2 is the expansion / contraction rate (%) when adherend B is heated from 23°C to 110°C.) Meet the adhesive sheet. Section 2 Item 2. The pressure-sensitive adhesive sheet according to item 1, wherein the pressure-sensitive adhesive composition contains a monofunctional monomer having a ring structure. Section 3 Item 3. The pressure-sensitive adhesive sheet according to item 1 or 2, wherein the pressure-sensitive adhesive composition contains 0.05 parts by mass or more and 5 parts by mass or less of the silane coupling agent relative to 100 parts by mass of the base agent. Section 4 The pressure-sensitive adhesive composition is a solvent-free type, Item 4. The pressure-sensitive adhesive sheet according to any one of items 1 to 3, wherein the pressure-sensitive adhesive layer has a crosslinked structure formed by a polyfunctional monomer. Section 5 Item 5. The pressure-sensitive adhesive sheet according to any one of items 1 to 4, wherein the pressure-sensitive adhesive composition contains an acrylic tackifier. Section 6 6. The pressure-sensitive adhesive sheet according to any one of items 1 to 5, having a thickness of 75 μm or more. Section 7 7. The pressure-sensitive adhesive sheet according to any one of items 1 to 6, wherein the adherend A or the adherend B, whichever has a higher stretch rate, has a thickness of 2 mm or more. Section 8 Item 8. The pressure-sensitive adhesive sheet according to any one of items 1 to 7, wherein the adherend A and the adherend B both have a total light transmittance of 50% or more. Section 9 Item 9. The pressure-sensitive adhesive sheet according to item 8, which is for use in car windows, building windows, or door windows. Item 10 Item 10. A laminate comprising the pressure-sensitive adhesive sheet according to any one of items 1 to 9 and a pair of adherends having different stretch rates. Effect of the Invention

[0010] The pressure-sensitive adhesive sheet according to the present invention is used for bonding adherends having different elasticity rates to each other, and is unlikely to peel off from the adherend even in environments where temperature changes occur or in high-temperature environments. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, embodiments of the present invention will be described in detail. In this specification, the expressions "containing" and "comprise" include the concepts of "containing", "comprises", "consists essentially of" and "consists only of".

[0012] The pressure-sensitive adhesive sheet of the present invention is used for bonding adherends having different stretch rates, and includes a pressure-sensitive adhesive layer obtained from a pressure-sensitive adhesive composition. Here, the pressure-sensitive adhesive composition contains at least a base agent containing a (meth)acrylic polymer and a silane coupling agent, the pressure-sensitive adhesive layer has a gel fraction of 80% or more, and the pressure-sensitive adhesive layer has a residual stress of 3.0 kPa or more and 10.0 kPa or less 60 seconds after application of a 15% torsional shear stress at 105°C. In addition, the pressure-sensitive adhesive sheet of the present invention has The following formula (1) |(X1-X2)|≧0.1% (1) (Here, when one of the pair of adherends is adherend A and the other is adherend B, X1 is the expansion / contraction rate (%) when adherend A is heated from 23°C to 110°C, and X2 is the expansion / contraction rate (%) when adherend B is heated from 23°C to 110°C.) Meet the following.

[0013] The adhesive sheet of the present invention is used to bond adherends having different elasticity rates to each other, and is unlikely to peel off from the adherend even in environments where temperature changes occur or in high-temperature environments.

[0014] As described above, the pressure-sensitive adhesive sheet of the present invention has an adhesive layer obtained from a pressure-sensitive adhesive composition. For example, when the pressure-sensitive adhesive composition is an active energy ray-curable type described below, the pressure-sensitive adhesive layer can be formed by irradiating the pressure-sensitive adhesive with active energy rays to cure it.

[0015] The pressure-sensitive adhesive composition for forming the pressure-sensitive adhesive layer contains at least a base agent containing a (meth)acrylic polymer and a silane coupling agent.

[0016] (Base material containing (meth)acrylic polymer) The base agent containing a (meth)acrylic polymer contains at least a (meth)acrylic polymer and is the main component of the pressure-sensitive adhesive composition. The base agent containing a (meth)acrylic polymer may be composed of only a (meth)acrylic polymer, or the base agent containing a (meth)acrylic polymer may contain a (meth)acrylic polymer and a monofunctional monomer described below. When the base agent containing a (meth)acrylic polymer contains a (meth)acrylic polymer and a monofunctional monomer, the base agent becomes a monomer solution of the (meth)acrylic polymer, which is a so-called syrup.

[0017] The (meth)acrylic polymer may be, for example, a wide variety of known acrylic polymers used to form pressure-sensitive adhesive sheets. For example, the (meth)acrylic polymer may be a polymer of a (meth)acrylic acid ester. That is, the (meth)acrylic polymer is a polymer having a (meth)acrylic acid ester unit.

[0018] Examples of the (meth)acrylic acid ester include (meth)acrylates having a linear or branched alkyl group, (meth)acrylates having a ring structure in the side chain, and (meth)acrylates having a hydroxyl group in the side chain.

[0019] In the (meth)acrylate having a linear or branched alkyl group, the alkyl group may have, for example, 1 to 20 carbon atoms, preferably 1 to 15 carbon atoms, more preferably 2 to 14 carbon atoms, and even more preferably 3 to 12 carbon atoms.

[0020] Specific examples of (meth)acrylates having a linear or branched alkyl group include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate, isopropyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, lauryl (meth)acrylate, cetyl (meth)acrylate, stearyl (meth)acrylate, and behenyl (meth)acrylate.

[0021] The (meth)acrylate having a ring structure in the side chain is preferably a (meth)acrylic monomer having an alicyclic or aromatic ring in the side chain, and more preferably a (meth)acrylic monomer having an alicyclic ring. Examples of the alicyclic ring include cyclopropane, cyclobutane, cyclopentane, cyclohexane, cycloheptane, cyclooctane, cyclononane, cyclodecane, cycloundecane, cyclododecane, norbornene, norbornadiene, dicyclopentane, isobornyl, tetrahydrofuran, and tetrahydropyran. The alicyclic ring may have a spiro structure. Examples of the aromatic ring include benzene, naphthalene, anthracene, pyridine, furan, benzofuran, pyrrole, thiophene, imidazole, and oxazole. Among them, the ring structure is preferably an alicyclic ring, more preferably at least one selected from cyclohexane, dicyclopentane, isobornyl, and benzene, and particularly preferably cyclohexane or isobornyl. The above-mentioned ring structure may further have a substituent. Examples of the substituent include substitutable substituents selected from a halogen atom, a halogenated alkyl group, an alkyl group, an alkenyl group, an acyl group, a hydroxy group, a hydroxyalkyl group, an alkoxy group, an aryl group, a heteroaryl group, an alicyclic group, a cyano group, an epoxy group, an oxetanyl group, a mercapto group, an amino group, and a (meth)acryloyl group.

[0022] The (meth)acrylate having a ring structure in the side chain preferably has a structure in which a monovalent group having a ring structure is bonded to an ester oxygen of the (meth)acrylate, and in this case, the monovalent group having a ring structure preferably has 3 to 12 carbon atoms, more preferably 4 to 10 carbon atoms, and even more preferably 4 to 8 carbon atoms.

[0023] Specific examples of the (meth)acrylate having a ring structure in the side chain include cyclohexyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, isobornyl (meth)acrylate, benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, 3-phenoxybenzyl (meth)acrylate, O-phenylphenoxyethyl (meth)acrylate, etc. Among them, the (meth)acrylate having a ring structure in the side chain is preferably at least one selected from the group consisting of cyclohexyl (meth)acrylate and isobornyl (meth)acrylate, in that peeling between the adherend and the pressure-sensitive adhesive sheet is unlikely to occur even under temperature change and high temperature environments.

[0024] Examples of the (meth)acrylate having a hydroxyl group in the side chain include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 3-chloro-2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 5-hydroxypentyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2,2-dimethyl 2-hydroxyethyl (meth)acrylate, 3-chloro 2-hydroxypropyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, and polyalkylene glycol mono(meth)acrylate.

[0025] The (meth)acrylic polymer may have other monomer units other than the above-mentioned (meth)acrylic acid esters. Examples of such monomer units include carboxyl group-containing (meth)acrylate units such as (meth)acrylic acid, glycidyl group-containing (meth)acrylate units, amino group-containing (meth)acrylate units, and monomer units based on (meth)acrylamide, allylamine, etc.

[0026] In terms of the fact that peeling between the adherend and the pressure-sensitive adhesive sheet does not easily occur even under temperature change and high temperature conditions, the (meth)acrylic polymer is preferably a polymer of a monomer containing at least one selected from the group consisting of (meth)acrylates having at least a linear or branched alkyl group, (meth)acrylates having a ring structure in the side chain, and (meth)acrylates having a hydroxyl group in the side chain. That is, the (meth)acrylic polymer preferably contains at least one monomer unit selected from the group consisting of (meth)acrylate units having at least a linear or branched alkyl group, (meth)acrylate units having a ring structure in the side chain, and (meth)acrylate units having a hydroxyl group in the side chain. In particular, the (meth)acrylic polymer preferably contains at least (meth)acrylate units having a linear or branched alkyl group.

[0027] The (meth)acrylic polymer preferably contains 30% by mass or more of (meth)acrylate units having a linear or branched alkyl group, more preferably 40% by mass or more, and even more preferably 50% by mass or more, and more preferably 90% by mass or less, even more preferably 85% by mass or less, and particularly preferably 80% by mass or less.

[0028] The (meth)acrylic polymer preferably contains 1% by mass or more of a (meth)acrylate having a ring structure in a side chain, more preferably 3% by mass or more, and even more preferably 5% by mass or more, more preferably 50% by mass or less, even more preferably 40% by mass or less, and particularly preferably 30% by mass or less.

[0029] The (meth)acrylic polymer preferably contains 10% by mass or more of (meth)acrylate units having a hydroxyl group in a side chain, more preferably 15% by mass or more, and even more preferably 20% by mass or more, and more preferably 50% by mass or less, even more preferably 45% by mass or less, and particularly preferably 40% by mass or less.

[0030] The (meth)acrylic polymer may contain other monomer units than those described above, so long as the effects of the present invention are not impaired. The content of the other monomer units in the (meth)acrylic polymer may be 20% by mass or less, preferably 15% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less.

[0031] The ratio (molar ratio) of each structural unit in the (meth)acrylic polymer can be considered to be the same as the molar ratio of each monomer used in producing the polymer.

[0032] The (meth)acrylic polymer may be composed of only one type of monomer unit selected from the group consisting of (meth)acrylate units having a linear or branched alkyl group, (meth)acrylate units having a ring structure in a side chain, and (meth)acrylate units having a hydroxyl group in a side chain.

[0033] The weight average molecular weight of the (meth)acrylic polymer is preferably more than 10,000, more preferably 100,000 or more, and even more preferably 200,000 or more. The weight average molecular weight of the (meth)acrylic polymer is preferably 2,000,000 or less, more preferably 1,500,000 or less, and even more preferably 1,200,000 or less.

[0034] The weight average molecular weight in the present invention refers to the weight average molecular weight in terms of polystyrene measured by gel permeation chromatography (GPC). There is no particular restriction on the GPC device used in the GPC method, and a commercially available GPC measuring device, for example, LC-2000Plus series manufactured by JASCO Corporation, and RI-2031Plus, UV-2075Plus, etc. as a detector can be used. In this case, for example, a GPC column consisting of four columns of "Shodex KF801", "Shodex KF803L", "Shodex KF800L" and "Shodex KF800D" manufactured by Showa Denko K.K. is used. The column temperature can be set to 40°C. Tetrahydrofuran is used as the eluent, and the measurement is performed at a flow rate of 1.0 ml / min. Usually, a calibration curve is prepared using standard polystyrene, and the weight average molecular weight (Mw) can be obtained by polystyrene conversion.

[0035] The (meth)acrylic polymer can be produced by a known method. For example, the (meth)acrylic polymer can be produced by polymerizing a monomer mixture for forming each constituent unit by a known polymerization method. The (meth)acrylic polymer may be a partial polymer, that is, a state in which a part of the monomer used for polymerization remains unpolymerized, that is, the above-mentioned syrup state. In this case, it is clear that the monomer contained in the syrup is a part of the monomer used during polymerization of the (meth)acrylic polymer. For example, solution polymerization, bulk polymerization, suspension polymerization, emulsion polymerization, etc. can be adopted as the polymerization method. The acrylic polymer can also be obtained from a commercial product, etc.

[0036] In the pressure-sensitive adhesive composition, the base agent can be in the form of a syrup (in the form of a partial polymer of a (meth)acrylic polymer) as described above, that is, the base agent can be a monofunctional monomer solution of the (meth)acrylic polymer. In the case of such a monofunctional monomer solution, the polymer fraction (the content ratio of the polymer to the total mass of the polymer and the monofunctional monomer) can be, for example, 1 to 50 mass%, and preferably 5 to 30 mass%. The base agent may consist of only the (meth)acrylic polymer and the monofunctional monomer.

[0037] The type of monofunctional monomer is not particularly limited, and examples thereof include various monomers used to form the (meth)acrylic polymer, that is, the above-mentioned (meth)acrylic acid esters, specifically, (meth)acrylates having a linear or branched alkyl group, (meth)acrylates having a ring structure in the side chain, (meth)acrylates having a hydroxyl group in the side chain, and the like.

[0038] (Silane coupling agent) Examples of the silane coupling agent include mercapto-based silane coupling agents containing a mercapto group, epoxy-based silane coupling agents having an epoxy group, vinyl-based silane coupling agents having a vinyl group, and isocyanurate-based silane coupling agents. Commercially available silane coupling agents can also be used. Examples of commercially available products include KBM-802, X-12-1056ES, KBM-402, KBM-403, KBM-5103, KBM-502, KBM-503, and KBM-9659 manufactured by Shin-Etsu Chemical Co., Ltd. By including a silane coupling agent in the adhesive composition, the adhesive sheet formed from the adhesive composition can have a higher adhesion to the adherend.

[0039] When the adhesive composition contains a silane coupling agent, its content is not particularly limited.In order to prevent the peeling between the adherend and the adhesive sheet from occurring even under temperature change and high temperature conditions, the content of the silane coupling agent is preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, even more preferably 0.15 parts by mass or more, and particularly preferably 0.2 parts by mass or more, and is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, even more preferably 2 parts by mass or less, and particularly preferably 1 part by mass or less, relative to 100 parts by mass of the main agent.

[0040] <Tackifier> The pressure-sensitive adhesive composition may further contain a tackifier. When the pressure-sensitive adhesive composition contains a tackifier, the pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition tends to have better adhesion to an adherend.

[0041] The type of tackifier is not particularly limited, and for example, a wide variety of tackifiers used in known pressure-sensitive adhesive sheets can be applied.

[0042] Among them, the tackifier is preferably an acrylic tackifier, that is, the pressure-sensitive adhesive composition preferably contains an acrylic tackifier.

[0043] The acrylic tackifier may be a resin having a glass transition temperature of 20° C. or higher. The glass transition temperature of the acrylic tackifier is preferably 30° C. or higher, more preferably 40° C. or higher, and even more preferably 50° C. or higher, and is preferably 200° C. or lower, more preferably 180° C. or lower, and even more preferably 150° C. or lower. By setting the glass transition temperature of the acrylic tackifier within the above range, the adhesion of the pressure-sensitive adhesive sheet to the adherend can be improved.

[0044] The structural unit contained in the acrylic tackifier may include a monomer unit having an alicyclic ring. When the acrylic tackifier includes a monomer unit having an alicyclic ring, the number of carbon atoms constituting the alicyclic ring is preferably 6 or more. Examples of the alicyclic ring having 6 or more carbon atoms include cyclohexane, cycloheptane, cyclooctane, cyclononane, cyclodecane, cycloundecane, cyclododecane, norbornene, norbornadiene, isobornyl, and dicyclopentane. Examples of the monomer having an alicyclic ring that can be preferably used include isobornyl (meth)acrylate, dicyclopentanyl (meth)acrylate, and dicyclopentenyl (meth)acrylate.

[0045] The acrylic tackifier can contain an alkyl (meth)acrylate unit instead of the monomer unit having an alicyclic ring or together with the monomer unit having an alicyclic ring. Examples of the alkyl (meth)acrylate include alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, lauryl (meth)acrylate, cetyl (meth)acrylate, stearyl (meth)acrylate, and behenyl (meth)acrylate. Among them, it is preferable that the acrylic tackifier contains methyl (meth)acrylate.

[0046] The acrylic tackifier is preferably a copolymer containing both an alicyclic monomer unit and an alkyl (meth)acrylate unit. In order to easily improve the adhesion between the pressure-sensitive adhesive sheet and the adherend, the content of the alkyl (meth)acrylate unit relative to the total mass of the acrylic tackifier is preferably 5% by mass or more, more preferably 10% by mass or more, and is preferably 90% by mass or less, more preferably 80% by mass or less.

[0047] The acrylic tackifier may have other monomer units as necessary. The other monomers may be any monomers that can be copolymerized with the above-mentioned alkyl (meth)acrylates, and examples of such monomers include (meth)acrylonitrile, vinyl acetate, vinyl chloride, and ethyl vinyl ether. The content of other monomer units in the acrylic tackifier is preferably 10% by mass or less, and more preferably 5% by mass or less.

[0048] The weight average molecular weight of the tackifier is preferably 3000 or more, more preferably 3200 or more, and even more preferably 3500 or more. The weight average molecular weight of the tackifier may be 20000 or less, more preferably 15000 or less, and even more preferably 10000 or less. The weight average molecular weight of the tackifier is a value measured by gel permeation chromatography (GPC) and calculated using a calibration curve prepared using standard polystyrene with a known molecular weight. As such a resin, a commercially available product may be used, or a product synthesized by a known method may be used.

[0049] The content of the tackifier in the pressure-sensitive adhesive composition is not particularly limited. In terms of easily improving the adhesion of the pressure-sensitive adhesive sheet to the adherend, the content of the tackifier is preferably 1 part by mass or more, more preferably 2 parts by mass or more, and is preferably 50 parts by mass or less, more preferably 30 parts by mass or less, and even more preferably 20 parts by mass or less, relative to 100 parts by mass of the base agent.

[0050] The tackifier may be formed only from an acrylic tackifier, or may contain other components in addition to the acrylic tackifier. The tackifier contained in the pressure-sensitive adhesive composition may be one type alone or two or more types.

[0051] <Polyfunctional Monomer> The adhesive composition may contain a polyfunctional monomer. Examples of such polyfunctional monomers include compounds having two or more polymerizable double bonds in the molecule. The number of polymerizable double bonds (e.g., radically polymerizable double bonds) in the polyfunctional monomer is two or more, preferably two or more and less than five, and more preferably two or more and less than four. When the adhesive composition contains a polyfunctional monomer, it may react with a monomer in the syrup to form, for example, a crosslinked polymer. That is, when the adhesive composition contains a polyfunctional monomer, the resulting adhesive layer may have a crosslinked structure due to the polyfunctional monomer.

[0052] When the pressure-sensitive adhesive composition contains a polyfunctional monomer, the resulting pressure-sensitive adhesive sheet is particularly resistant to peeling between the adherend and the pressure-sensitive adhesive sheet even when placed in an environment of changing temperature or in a high-temperature environment.

[0053] Examples of the polyfunctional monomer include bifunctional monomers (monomers having two polymerizable double bonds), such as polyethylene glycol diacrylate, polypropylene diacrylate, alkyl diacrylate, polytetramethylene glycol diacrylate, polypropylene glycol diacrylate, dioxane diacrylate, tricyclodecanol diacrylate, and fluorene diacrylate. Examples of the polyfunctional monomer include trifunctional or higher monomers, such as alkoxylated trimethylolpropane triacrylate, alkoxylated glycerin triacrylate, caprolactone-modified isocyanurate triacrylate, pentaerythritol acrylate, alkoxylated pentaerythritol acrylate, (alkoxylated) pentaerythritol acrylate, (alkoxylated) ditrimethylolpropane acrylate, (alkoxylated) dipentaerythritol acrylate, and (ethoxylated) polyglycerin acrylate.

[0054] The polyfunctional monomer may have a bisphenol skeleton in one molecule. Examples of such polyfunctional monomers include diacrylate of bisphenol A diglycidyl ether, diacrylate of propoxylated bisphenol A, and diacrylate of bisphenol F diglycidyl ether.

[0055] The polyfunctional monomer may be, for example, a commercially available product. Examples of commercially available products include "A-200" (polyethylene glycol #200 diacrylate), "A-400" (polyethylene glycol #400 diacrylate), and "A-600" (polyethylene glycol #600 diacrylate) from the NK Ester series, which are bifunctional polyethylene glycol acrylates manufactured by Shin-Nakamura Chemical Co., Ltd., trifunctional monomer A-TMPT ((alkoxylated) trimethylolpropane acrylate), trifunctional monomer M310 (trimethylolpropane PO modified triacrylate) and trifunctional monomer M321 (trimethylolpropane propylene oxide modified triacrylate) manufactured by Toagosei Co., Ltd., bifunctional monomer M211B (bisphenol A EO modified diacrylate), M240 (polyethylene glycol diacrylate), and tetrafunctional monomer M-408 (ditrimethylolpropane tetraacrylate) manufactured by Toagosei Co., Ltd. Other commercially available polyfunctional monomers include, for example, A-DOG, A-DCP, A-9300, and A-9200YN manufactured by Shin-Nakamura Chemical Co., Ltd., FA-731A manufactured by Hitachi Chemical Co., Ltd., and AOMA manufactured by Nippon Shokubai.

[0056] In the pressure-sensitive adhesive composition, the content ratio of the polyfunctional monomer is not particularly limited. In order to prevent peeling between the adherend and the pressure-sensitive adhesive sheet even under a temperature change environment and a high temperature environment, the content ratio of the polyfunctional monomer is preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, even more preferably 0.15 parts by mass or more, and particularly preferably 0.2 parts by mass or more, and is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, even more preferably 2 parts by mass or less, and particularly preferably 1 part by mass or less, relative to 100 parts by mass of the main agent. By having the content of the polyfunctional monomer within the above range, it becomes easy to control the residual stress 60 seconds after applying a 15% torsional shear stress at 105 ° C. to a desired range.

[0057] The pressure-sensitive adhesive composition may contain one type of polyfunctional monomer alone, or two or more types of polyfunctional monomers.

[0058] <Additional monofunctional monomer> The adhesive composition may contain an additional monofunctional monomer. As described above, when the base agent is a syrup (for example, when it is a partial polymer), the base agent contains a (meth)acrylic polymer and a part of the monomer (monofunctional monomer) used when polymerizing the polymer, and in addition to this, the adhesive composition may further contain an additional monofunctional monomer. Therefore, in this specification, "monofunctional monomer" means a monomer derived from a partial polymer of a (meth)acrylic polymer, while "additional monofunctional monomer" may mean a monomer other than the monomer derived from a partial polymer of a (meth)acrylic polymer. The additional monofunctional monomer may be the same type as the monomer derived from the partial polymer of a (meth)acrylic polymer, or may be a different type.

[0059] The type of the additional monofunctional monomer is not particularly limited, and can be a wide variety of known monofunctional monomers that are used in pressure-sensitive adhesive sheets. Among them, the additional monofunctional monomer preferably has a ring structure. That is, the pressure-sensitive adhesive composition preferably contains a monofunctional monomer having a ring structure. In this case, the obtained pressure-sensitive adhesive sheet is likely to be prevented from peeling off from the adherend even when placed in a temperature-changing environment and a high-temperature environment.

[0060] The monofunctional monomer having a ring structure is more preferably a (meth)acrylate having a ring structure in a side chain. In the (meth)acrylate having a ring structure in a side chain, the number of carbon atoms in the ring structure is preferably 3 or more, more preferably 4 or more, even more preferably 5 or more, even more preferably 6 or more, and is preferably 18 or less, more preferably 14 or less, even more preferably 12 or less, and particularly preferably 11 or less.

[0061] Specific examples of the additional monofunctional monomer include cyclohexyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, isobornyl (meth)acrylate, benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, 3-phenoxybenzyl (meth)acrylate, O-phenylphenoxyethyl (meth)acrylate, etc. Among them, the additional monofunctional monomer is preferably at least one selected from the group consisting of dicyclopentanyl (meth)acrylate and isobornyl (meth)acrylate, in that peeling between the adherend and the pressure-sensitive adhesive sheet is unlikely to occur even under temperature change and high temperature environments.

[0062] The content of the additional monofunctional monomer in the pressure-sensitive adhesive composition is not particularly limited. In terms of easily improving the adhesion of the pressure-sensitive adhesive sheet to the adherend, the content of the additional monofunctional monomer is preferably 1 part by mass or more, more preferably 2 parts by mass or more, even more preferably 3 parts by mass or more, particularly preferably 5 parts by mass or more, and is preferably 50 parts by mass or less, more preferably 40 parts by mass or less, even more preferably 30 parts by mass or less, and particularly preferably 25 parts by mass or less, relative to 100 parts by mass of the main agent.

[0063] The additional monofunctional monomer contained in the pressure-sensitive adhesive composition may be one type alone or two or more types.

[0064] <Photopolymerization initiator> The pressure-sensitive adhesive composition may further include a photopolymerization initiator. The photopolymerization initiator initiates polymerization of the polyfunctional monomer by irradiation with active energy rays. In this specification, the term "active energy rays" refers to electromagnetic waves or charged particle rays having an energy quantum, and examples of such rays include ultraviolet rays, electron beams, visible light, X-rays, and ion beams. Among these, ultraviolet rays or electron beams are preferred from the viewpoint of versatility, and ultraviolet rays are particularly preferred.

[0065] The type of photopolymerization initiator is not particularly limited, and a wide variety of known photopolymerization initiators can be used. Examples of the photopolymerization initiator include acetophenone-based photopolymerization initiators such as 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxycyclohexyl-phenyl ketone, 2-hydroxy-2-methyl-1-phenylpropanone, 1-[4-(2-hydroxyethoxyl)-phenyl]-2-hydroxy-methylpropanone, and 2-hydroxy-1-(4-(4-(2-hydroxy-2-methylpropionyl)benzyl)phenyl)-2-methyl-1-propanone; acylphosphine oxide-based photopolymerization initiators such as 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and 2,4,6-trimethylbenzoyl)phenylphosphine oxide; intramolecular hydrogen abstraction photopolymerization initiators such as methyl benzoylformate and 4-methylbenzophenone; and oil-soluble polymerization initiators such as oxime ester-based photopolymerization initiators and cationic photopolymerization initiators. Among them, the photopolymerization initiator is preferably at least one selected from the group consisting of acetophenone-based photopolymerization initiators, acylphosphine oxide-based photopolymerization initiators, and oxime ester-based photopolymerization initiators.

[0066] Commercially available acetophenone-based photopolymerization initiators include EsacureOne (oligo(2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenylpropanone], photoinitiator manufactured by IGM RESINS BV), Omnirad651 (2,2-dimethoxy-2-phenylacetophenone, manufactured by IGM RESINS BV), Omnirad184 (1-hydroxycyclohexyl-phenylketone, manufactured by IGM RESINS BV), and Omnirad1173 (2-hydroxy-2-methyl-1-phenylpropanone, manufactured by IGM RESINS BV). Commercially available acylphosphine oxide-based photopolymerization initiators include Omnirad 819 (bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, manufactured by IGM RESINS BV) and Omnirad TPO (2,4,6-trimethylbenzoyl-diphenylphosphine oxide, manufactured by IGM RESINS BV). (manufactured by RESINS BV)

[0067] In the pressure-sensitive adhesive composition, the content ratio of the photopolymerization initiator is not particularly limited, and is, for example, preferably 0.01 parts by mass or more, more preferably 0.05 parts by mass or more, and even more preferably 0.1 parts by mass or more, relative to 100 parts by mass of the main agent, and is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, even more preferably 3 parts by mass or less, and particularly preferably 1.5 parts by mass or less.

[0068] <Adhesive composition> The adhesive composition contains at least the (meth)acrylic polymer and a silane coupling agent, and may further contain one or more selected from the group consisting of a tackifier, a polyfunctional monomer, a monofunctional monomer, and a photopolymerization initiator, as necessary. The adhesive composition may contain other components to the extent that the effects of the present invention are not impaired. Examples of other components include crosslinkers, solvents, plasticizers, antioxidants, metal corrosion inhibitors, ultraviolet absorbers, and light stabilizers. Dyes and pigments may also be added for the purpose of coloring.

[0069] The crosslinking agent can be appropriately selected, for example, taking into consideration the reactivity with the crosslinkable functional group of the (meth)acrylic polymer, and can be a wide variety of known crosslinking agents contained in the pressure-sensitive adhesive sheet. Specific examples of the crosslinking agent can be selected from known crosslinking agents such as isocyanate compounds, epoxy compounds, oxazoline compounds, aziridine compounds, metal chelate compounds, and butylated melamine compounds. Among them, the crosslinking agent preferably contains at least one selected from isocyanate compounds, epoxy compounds, and metal chelate compounds.

[0070] When the pressure-sensitive adhesive composition contains a solvent, examples of the solvent include hydrocarbons other than polymerizable monomers, such as hexane, heptane, octane, toluene, xylene, ethylbenzene, cyclohexane, and methylcyclohexane; alcohols, such as methanol, ethanol, propanol, isopropyl alcohol, butanol, isobutyl alcohol, and diacetone alcohol; ethers, such as diethyl ether, diisopropyl ether, dioxane, and tetrahydrofuran; ketones, such as acetone, methyl ethyl ketone, methyl isobutyl ketone, isophorone, and cyclohexanone; esters, such as methyl acetate, ethyl acetate, butyl acetate, isobutyl acetate, amyl acetate, and ethyl butyrate; and polyols, such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monomethyl ether acetate, propylene glycol monomethyl ether, propylene glycol monoethyl ether, and propylene glycol monomethyl ether acetate, and derivatives thereof.

[0071] The adhesive composition is preferably a solvent-free type. In this case, the adhesive composition preferably contains a polyfunctional monomer. That is, the adhesive composition is a solvent-free type, and the adhesive layer preferably has a crosslinked structure by the polyfunctional monomer. The preparation method of the adhesive composition is not particularly limited, and for example, a known method can be widely adopted.

[0072] The pressure-sensitive adhesive composition is preferably a so-called active energy ray curable type having a property of being cured by irradiation with active energy rays. In this case, the pressure-sensitive adhesive composition contains a photopolymerization initiator and a component (e.g., the above-mentioned monofunctional monomer, additional monofunctional monomer, and polyfunctional monomer) whose polymerization is initiated by the photopolymerization initiator.

[0073] (Adhesive sheet) The pressure-sensitive adhesive sheet of the present invention is obtained by forming the pressure-sensitive adhesive composition into a sheet, that is, it has a pressure-sensitive adhesive layer containing a cured product of the pressure-sensitive adhesive composition.

[0074] The pressure-sensitive adhesive layer can be formed by curing the pressure-sensitive adhesive composition. The method for curing the pressure-sensitive adhesive composition is not particularly limited, and for example, a known method can be widely adopted. Specifically, the method can include a step of applying the pressure-sensitive adhesive composition to a substrate to form a coating film, and a step of irradiating the coating film with active energy rays to obtain a cured product of the pressure-sensitive adhesive. This allows the pressure-sensitive adhesive layer to be formed by curing the pressure-sensitive adhesive.

[0075] The pressure-sensitive adhesive composition can be applied using a known coating device, such as a blade coater, an air knife coater, a roll coater, a bar coater, a gravure coater, a microgravure coater, a rod blade coater, a lip coater, a die coater, or a curtain coater.

[0076] When applying the adhesive composition, the substrate used is not particularly limited. For example, the adhesive composition can be applied to various substrates such as a resin substrate or a glass substrate. When the substrate has a release sheet as described below, the adhesive composition can be applied onto the release sheet. The adhesive composition can also be applied directly onto a member to be adhered. The thickness of the adhesive composition after application is not particularly limited, and can be appropriately set according to the desired thickness of the adhesive layer (or adhesive sheet). After forming the coating film, the coating film may be subjected to a heating treatment or a drying treatment as necessary.

[0077] The step of irradiating the coating film with active energy rays can be, for example, the same as a known method. In this step, the photopolymerization initiator in the pressure-sensitive adhesive composition generates radicals by the active energy rays, and the polymerizable components in the pressure-sensitive adhesive composition (for example, monomers, polyfunctional monomers, etc. in the pressure-sensitive adhesive composition) initiate and progress a polymerization reaction by the generated radicals, thereby becoming a polymerized cured product. This forms a pressure-sensitive adhesive layer and also improves the adhesive strength.

[0078] Examples of active energy rays include ultraviolet rays, electron beams, visible light, X-rays, ion beams, etc., and can be appropriately selected depending on the photopolymerization initiator contained in the pressure-sensitive adhesive composition. Among them, from the viewpoint of versatility, ultraviolet rays or electron beams are preferred, and ultraviolet rays are particularly preferred. Examples of light sources for ultraviolet rays include chemical lamps, high-pressure mercury lamps, low-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, carbon arcs, xenon arcs, and electrodeless ultraviolet lamps. The irradiation output of ultraviolet rays is an integrated light amount of 100 to 10,000 mJ / cm. 2 It is preferable to set the range to 200 to 5000 mJ / cm 2 In the step of irradiating the coating film with active energy rays, the active energy rays may be irradiated in two stages.

[0079] The cured product formed as described above can be used as the pressure-sensitive adhesive layer of the pressure-sensitive adhesive sheet of the present invention. The pressure-sensitive adhesive layer may consist of only the cured product of the pressure-sensitive adhesive, or may contain other components in addition to the cured product of the pressure-sensitive adhesive.

[0080] The pressure-sensitive adhesive sheet of the present invention may have other layers as long as it has the pressure-sensitive adhesive layer, or may be formed only of the pressure-sensitive adhesive layer. That is, the pressure-sensitive adhesive sheet preferably consists of only the pressure-sensitive adhesive layer. The pressure-sensitive adhesive layer has, for example, a single-layer structure.

[0081] The gel fraction of the pressure-sensitive adhesive layer is 80% or more. If the gel fraction of the pressure-sensitive adhesive layer is less than 80%, peeling between the adherend and the pressure-sensitive adhesive sheet is likely to occur when placed in a temperature change environment or a high temperature environment. The gel fraction of the pressure-sensitive adhesive layer is preferably 82% or more, more preferably 84% or more, and is preferably 98% or less, more preferably 95% or less.

[0082] The gel fraction of the adhesive layer is a value measured by the following method. First, about 0.1 g of the adhesive sheet (adhesive layer) is placed in a sample bottle, 30 ml of ethyl acetate is added, and the mixture is shaken for 24 hours. The contents of the sample bottle are then filtered through a 200-mesh stainless steel wire screen, and the residue on the screen is dried at 120°C for 1 hour to measure the dry mass (g). The gel fraction is calculated from the obtained dry mass using the following formula: Gel fraction (mass%) = (dry mass / collected mass of adhesive sheet) × 100 Equation 1 Calculate the gel fraction using 1.

[0083] The pressure-sensitive adhesive layer has a residual stress of 3.0 kPa or more and 10.0 kPa or less 60 seconds after application of a 15% torsional shear stress at 105° C. Hereinafter, the residual stress 60 seconds after application of a 15% torsional shear stress at 105° C. will be referred to simply as "residual stress after 60 seconds."

[0084] If the residual stress of the adhesive layer after 60 seconds is less than 3.0 kPa or exceeds 10.0 kPa, peeling between the adherend and the adhesive sheet is likely to occur when placed in a temperature changing environment or a high temperature environment. The residual stress of the adhesive layer after 60 seconds is preferably 3.5 kPa or more, and more preferably 9 kPa or less, more preferably 8 kPa or less, and even more preferably 7 kPa or less.

[0085] The residual stress of the adhesive layer after 60 seconds can be measured using a laminated sheet of the adhesive layer laminated to a thickness of 1000 μm. Specifically, the laminated sheet is pressurized in an autoclave under an atmosphere of 30° C. and 0.5 MPa for 10 minutes to obtain a measurement sample. The obtained measurement sample is subjected to a probe diameter of 8 mm and an initial heating temperature of 105° C. for 2 minutes, and then a 15% torsional strain is applied to the obtained measurement sample while maintaining the temperature at 105° C., and the shear stress is read 1 minute after the load. This shear stress is the residual stress of the adhesive layer after 60 seconds.

[0086] The thickness of the adhesive layer is preferably 75 μm or more. In this case, even when placed in a high temperature change environment and a warm environment, peeling between the adherend and the adhesive sheet tends to be difficult. The thickness of the adhesive layer is more preferably 80 μm or more, even more preferably 90 μm or more, and particularly preferably 100 μm or more, and is preferably 1000 μm or less, more preferably 500 μm or less, and even more preferably 400 μm or less.

[0087] The pressure-sensitive adhesive sheet of the present invention may also be a pressure-sensitive adhesive sheet provided with a base material such as a release sheet on one or both sides. That is, the present invention also includes a pressure-sensitive adhesive sheet with a release sheet provided with a pressure-sensitive adhesive sheet and a release sheet.

[0088] The release sheet may be a release laminate sheet having a release sheet substrate and a release agent layer provided on one side of the release sheet substrate, or a polyolefin film such as a polyethylene film or a polypropylene film as a low polar substrate. Paper or a polymer film is used as the release sheet substrate in the release laminate sheet. For example, a general-purpose addition type or condensation type silicone-based release agent or a long-chain alkyl group-containing compound is used as the release agent constituting the release agent layer. A commercially available product may be used as the release laminate sheet. For example, a heavy separator film that is a release-treated polyethylene terephthalate film manufactured by Teijin DuPont Films Co., Ltd., or a light separator film that is a release-treated polyethylene terephthalate film manufactured by Teijin DuPont Films Co., Ltd., may be used.

[0089] The pressure-sensitive adhesive sheet of the present invention is used to bond a pair of adherends having different stretch rates. Here, when one of the pair of adherends is adherend A and the other is adherend B, the following formula (1) is satisfied: |(X1-X2)|≧0.1% (1) In formula (1), X1 is the expansion rate (%) when adherend A is heated from 23°C to 110°C, and X2 is the expansion rate (%) when adherend B is heated from 23°C to 110°C. When the expansion rate is x, x is {(length of adherend at 110°C - length of adherend at 23°C before heating) / length of adherend at 23°C before heating} x 100(%) The length of the adherend is, for example, the length in the MD or TD direction of the adherend.

[0090] In addition, in formula (1), there may be a directionality of the stretch rate in adherend A and adherend B (the stretch rate may differ depending on the direction). In such a case, the stretch rates in the directions in which the rate of change in the stretch rate when heated from 23°C to 110°C is large will be adopted as the values ​​of X1 and X2, respectively.

[0091] By bonding adherend A and adherend B that satisfy formula (1) with the pressure-sensitive adhesive sheet of the present invention, peeling between the adherend and the pressure-sensitive adhesive sheet is less likely to occur even when placed in a temperature changing environment or a high-temperature environment.

[0092] In formula (1), |(X1-X2)| is preferably ≧0.1%, more preferably ≧0.15%, and even more preferably ≧0.2%. The upper limit of |(X1-X2)| is preferably 1%.

[0093] Of the adherend A and the adherend B, the one having a higher expansion / contraction rate when heated from 23° C. to 110° C. preferably has a thickness of 2 mm or more. In this case, the pressure-sensitive adhesive sheet of the present invention can be suitably used for applications such as sunroofs for automobiles and large windows for buildings. The thicknesses of the adherend A and the adherend B can be, for example, 100 mm or less.

[0094] It is preferable that the total light transmittance of both the adherend A and the adherend B is 50% or more. In this case, the pressure-sensitive adhesive sheet of the present invention is suitable for applications requiring high transparency, and can be suitably used in applications such as sunroofs for automobiles and large windows for buildings.

[0095] The combination of the materials of the adherend A and the adherend B is not particularly limited, and various combinations can be mentioned as long as the formula (1) is satisfied. For example, when the adherend having a larger expansion rate (%) when heated from 23° C. to 110° C. is polycarbonate, examples of the adherend having a smaller expansion rate (%) when heated from 23° C. to 110° C. include glass, stretched polyethylene terephthalate, cycloolefin polymer film, TAC film, ITO vapor-deposited film, etc.

[0096] The pressure-sensitive adhesive sheet of the present invention can be used in various applications for bonding adherends together, and is particularly suitable for car windows and sunroofs, building window applications, and door windows. In particular, the pressure-sensitive adhesive sheet of the present invention is less likely to peel off from the adherend even when placed in a temperature-changing or high-temperature environment, and is therefore suitable for applications such as car sunroofs and large building windows.

[0097] The pressure-sensitive adhesive sheet of the present invention can be bonded to adherends to form a laminate. That is, the present invention includes a laminate comprising the pressure-sensitive adhesive sheet and a pair of adherends having different stretch rates.

[0098] One embodiment of the laminate is a laminate in which the adherend A, the pressure-sensitive adhesive sheet of the present invention, and the adherend B are laminated in this order. In this case, the pressure-sensitive adhesive sheet of the present invention is directly attached to the adherend A and the adherend B.

[0099] Since the laminate includes the pressure-sensitive adhesive sheet of the present invention, peeling between the adherend and the pressure-sensitive adhesive sheet is unlikely to occur even when placed in a temperature change environment or a high temperature environment, despite the different expansion and contraction rates of the adherend A and the adherend B. For example, even if the adherend with the larger expansion and contraction rate has a thickness of, for example, more than 2 mm, peeling of the pressure-sensitive adhesive sheet in the laminate is unlikely to occur.

[0100] In specifying the invention included in the present disclosure, the configurations (properties, structures, functions, etc.) described in each embodiment of the present disclosure may be combined in any manner. In other words, the present disclosure includes all subject matter consisting of all combinations of the configurations that can be combined as described in this specification. EXAMPLES

[0101] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the embodiments of these examples.

[0102] The following was prepared as a monomer (monofunctional monomer) for producing the "base material containing a (meth)acrylic polymer" used in each example. 2EHA: 2-Ethylhexyl acrylate ·BA: Butyl acrylate 4HBA: 4-Hydroxybutyl acrylate IBXA: Isobornyl acrylate CHMA: Cyclohexyl methacrylate

[0103] In addition, the following were prepared as the "multifunctional monomer," "additional monofunctional monomer," "silane coupling agent," and "photopolymerization initiator" used in each example.

[0104] (Polyfunctional Monomer) A-200: Bifunctional monomer (polyethylene glycol #200 diacrylate, Shin-Nakamura Chemical Co., Ltd., NK Ester A-200 (registered trademark)) A-600: Bifunctional monomer (polyethylene glycol #200 diacrylate, Shin-Nakamura Chemical Co., Ltd., NK Ester A-600 (registered trademark))

[0105] (Additional Monofunctional Monomer) IBXA: Isobornyl acrylate (Osaka Organic Chemical Industry Co., Ltd.) DCPA: Dicyclopentanyl acrylate (manufactured by Resonac)

[0106] (Silane coupling agent) ·KBM-9659 ("KBM-9659" (registered trademark) manufactured by Shin-Etsu Chemical Co., Ltd.) ·KBM-403 ("KBM-403" (registered trademark) manufactured by Shin-Etsu Chemical Co., Ltd.)

[0107] (Photopolymerization initiator) Esacure One (registered trademark) (IGM Resins BV, Esacure One (registered trademark))

[0108] (Production Example 1: Production of Tackifier a) 250g of methyl methacrylate, 250g of isobornyl methacrylate, 20g of n-dodecyl mercaptan, 500g of ethyl acetate, and 200g of methyl ethyl ketone were added to a 2L flask equipped with a stirrer, a nitrogen inlet tube, a cooling tube, and a thermometer, and nitrogen replacement was performed for 60 minutes at a nitrogen flow rate of 300ml / min, after which the nitrogen flow rate was reduced to 100ml / min, and the temperature was raised to 70°C in a water bath and heating was stopped. 2g of AIBN was added and reacted for 3 hours while controlling heat generation, after which 3g of AIBN was added, reacted for 4 hours, and then cooled to 30°C. Finally, the mixture was dried at 100°C for 5 hours to remove the solvent, and an acrylic tackifier a (referred to as tackifier resin a in Table 1) with a weight average molecular weight of 6,000 and a glass transition temperature of 85°C was obtained.

[0109] (Production Example 2: Production of Tackifier b) An acrylic tackifier b (referred to as tackifier resin b in Table 1) having a weight average molecular weight of 8,000 and a glass transition temperature of 95°C was obtained in the same manner as in Production Example 1, except that the amounts of methyl methacrylate, isobornyl methacrylate, and n-dodecyl mercaptan were changed to 200 g, 300 g, and 15 g, respectively.

[0110] (Production Example 3: Production of Tackifier c) An acrylic tackifier c (referred to as tackifier resin c in Table 1) having a weight average molecular weight of 6,000 and a glass transition temperature of 95°C was obtained in the same manner as in Production Example 1, except that 250 g of isobornyl methacrylate was changed to 250 g of dicyclopentanyl methacrylate.

[0111] The tackifiers obtained in Production Examples 1 to 3 were previously dried at 100° C. for 5 hours to remove the solvent before use in each Example.

[0112] Example 1 <Production of base agent containing (meth)acrylic polymer> A (meth)acrylic polymer (syrup) was synthesized according to the main composition containing the (meth)acrylic polymer shown in Table 1. Specifically, 100 parts by mass of a mixed monomer consisting of 2EHA, 4HBA, and IBXA (mass ratio 65:30:5) prepared in the amounts shown in Table 1 and 0.06 parts by mass of n-dodecyl mercaptan were charged into a 2L flask equipped with a stirrer, a nitrogen inlet tube, a cooling tube, and a thermometer, and nitrogen replacement was performed for 60 minutes at a nitrogen flow rate of 300 ml / min. Thereafter, the nitrogen flow rate was reduced to 100 ml / min, the temperature was raised to 65°C in a water bath, 0.15 g of AIBN was charged, and the reaction was allowed to proceed for 30 minutes while controlling the heat generation, and then the mixture was cooled to room temperature. Additional monomers were charged into the flask so that the monomer ratio was the above-mentioned mass ratio, and the solid concentration was adjusted to 20%. In this manner, a (meth)acrylic polymer syrup (a solution in which a (meth)acrylic polymer is dissolved in a monofunctional monomer) having a solid content of 20% by mass and a weight-average molecular weight of 900,000 was obtained as a base component.

[0113] <Production of Pressure-Sensitive Adhesive Composition> Next, a pressure-sensitive adhesive layer was obtained from a pressure-sensitive adhesive composition prepared according to the pressure-sensitive adhesive composition preparation conditions shown in Table 1. First, as shown in Table 1, 6 parts by mass of tackifier a (tackifier resin a) obtained in Production Example 1, 0.2 parts by mass of A-200 as a polyfunctional monomer, 5 parts by mass of IBXA as an additional monofunctional monomer (referred to as "monofunctional monomer" in Table 1), 0.3 parts by mass of KBM-9659 as a silane coupling agent, and 0.3 parts by mass of Esacure One as a photopolymerization initiator were added relative to a total amount of 100 parts by mass of the main agent, and the mixture was stirred and degassed to obtain pressure-sensitive adhesive composition 1.

[0114] <Production of adhesive sheets> The obtained pressure-sensitive adhesive composition 1 was applied to a thickness of 300 μm on a 100 μm thick polyester film (release sheet) coated with a silicone release agent, and then laminated with a 75 μm thick polyester film (release sheet) coated with a silicone release agent. The laminate was then exposed to a chemical lamp at an illumination intensity of 5 mW / cm. 2 , cumulative illuminance 750mJ / cm 2Then, a high-pressure mercury lamp was used to illuminate the sample at an illuminance of 200 mW / cm. 2 , cumulative illuminance 2000mJ / cm 2 An adhesive layer was formed by irradiating the surface of the substrate so as to obtain an adhesive sheet 1 having release sheets on both sides.

[0115] <Preparation of Laminate> As the adherend A, a polycarbonate plate ("PC-1600" manufactured by Takiron CI) with a thickness of 5 mm cut into a 15 cm square was prepared, and as the adherend B, a float glass (manufactured by Hiraoka Glass Industry Co., Ltd.) with a thickness of 1 mm cut into a 15 cm square was prepared. The adherend A was annealed in advance by putting it in a dryer at 95°C for 6 hours, and then one side of the annealed adherend A was corona treated. Such corona treatment was performed using a CORONA GENERATOR AGF-B10 (manufactured by Kasuga Electric Co., Ltd.) with an output of 0.14 kW, a speed of 5 m / min, and four treatments. Next, one of the polyester films bonded to the adhesive sheet 1 was peeled off, and the corona-treated surface of the adherend A was bonded to the exposed adhesive layer. Thereafter, the other polyester film of the adhesive sheet was peeled off, and the adherend B was bonded to the exposed adhesive layer to obtain a laminate. This laminate was pressure-bonded in an autoclave at a pressure of 0.5 kPa and a temperature of 30° C. for 30 minutes, and then allowed to stand at room temperature for one day to prepare a laminate for evaluation.

[0116] Example 2 <Production of base agent containing (meth)acrylic polymer> A syrup of a (meth)acrylic polymer was obtained as a base component in the same manner as in the production of a (meth)acrylic polymer in Example 1, except that the base component composition was changed to the conditions shown in Table 1.

[0117] <Production of Pressure-Sensitive Adhesive Composition> An adhesive composition 2 was obtained in the same manner as in the production of the adhesive composition of Example 1, except that the preparation conditions of the adhesive composition were changed to those shown in Table 1.

[0118] <Production of adhesive sheets> An adhesive sheet 2 was obtained in the same manner as in the production of the adhesive sheet in Example 1, except that, instead of adhesive composition 1, adhesive composition 2 was applied to a thickness of 175 μm.

[0119] <Preparation of Laminate> A laminate was obtained in the same manner as in the preparation of the laminate in Example 1, except that adhesive sheet 1 was changed to adhesive sheet 2 and adherend A was changed to a polycarbonate plate having a thickness of 3 mm.

[0120] Example 3 <Production of (meth)acrylic polymer> A syrup of a (meth)acrylic polymer was obtained as a base component in the same manner as in the production of a (meth)acrylic polymer in Example 1, except that the base component composition was changed to the conditions shown in Table 1.

[0121] <Production of Pressure-Sensitive Adhesive Composition> Pressure-sensitive adhesive composition 3 was obtained in the same manner as in the production of the pressure-sensitive adhesive composition of Example 1, except that the conditions for preparing the pressure-sensitive adhesive composition were changed to those shown in Table 1.

[0122] <Production of adhesive sheets> An adhesive sheet 3 was obtained in the same manner as in the production of the adhesive sheet in Example 1, except that adhesive composition 3 was applied in place of adhesive composition 1 so as to give a thickness of 250 μm.

[0123] <Preparation of Laminate> A laminate was obtained in the same manner as in the preparation of the laminate in Example 1, except that the adhesive sheet 1 was changed to the adhesive sheet 3.

[0124] Example 4 <Production of (meth)acrylic polymer> A syrup of a (meth)acrylic polymer was obtained as a base component in the same manner as in the production of a (meth)acrylic polymer in Example 1, except that the base component composition was changed to the conditions shown in Table 1.

[0125] <Production of Pressure-Sensitive Adhesive Composition> Pressure-sensitive adhesive composition 4 was obtained in the same manner as in the production of the pressure-sensitive adhesive composition of Example 1, except that the conditions for preparing the pressure-sensitive adhesive composition were changed to those shown in Table 1.

[0126] <Production of adhesive sheets> An adhesive sheet 4 was obtained in the same manner as in the production of the adhesive sheet in Example 1, except that the adhesive composition 4 obtained was used instead of the adhesive composition 1.

[0127] <Preparation of Laminate> A laminate was obtained in the same manner as in Example 1, except that the adhesive sheet 1 was changed to the adhesive sheet 4, the adherend A was changed to a polycarbonate plate having a thickness of 3 mm, and the adherend B was changed to a polyethylene terephthalate film having a thickness of 0.1 mm ("A4360" manufactured by Toyobo Co., Ltd.). In producing this laminate, the two were attached together so that the adhesive surface of the polyethylene terephthalate film was in contact with the adhesive sheet (adhesive layer).

[0128] Example 5 <Production of (meth)acrylic polymer> A syrup of a (meth)acrylic polymer was obtained as a base component in the same manner as in the production of a (meth)acrylic polymer in Example 1, except that the base component composition was changed to the conditions shown in Table 1.

[0129] <Production of Pressure-Sensitive Adhesive Composition> Pressure-sensitive adhesive composition 5 was obtained in the same manner as in the production of the pressure-sensitive adhesive composition of Example 1, except that the conditions for preparing the pressure-sensitive adhesive composition were changed to those shown in Table 1.

[0130] <Production of adhesive sheets> An adhesive sheet 5 was obtained in the same manner as in the production of the adhesive sheet in Example 1, except that, instead of adhesive composition 1, adhesive composition 5 was applied to a thickness of 100 μm.

[0131] <Preparation of Laminate> A laminate was obtained in the same manner as in Example 1, except that the adhesive sheet 1 was changed to adhesive sheet 5, the adherend A was changed to a polycarbonate plate having a thickness of 2 mm (Mitsubishi Gas Chemical Company, MRS58TB), and the adherend B was changed to a heat shielding film having a thickness of 0.05 mm (Geomatec's "ITO vapor deposition film"). In producing this laminate, the adhesive sheet (adhesive layer) and the heat shielding film were attached together so that the ITO surface of the heat shielding film was in contact with the adhesive sheet (adhesive layer).

[0132] Example 6 <Production of (meth)acrylic polymer> A syrup of a (meth)acrylic polymer was obtained as a base component in the same manner as in the production of a (meth)acrylic polymer in Example 1, except that the base component composition was changed to the conditions shown in Table 1.

[0133] <Production of Pressure-Sensitive Adhesive Composition> Pressure-sensitive adhesive composition 6 was obtained in the same manner as in the production of the pressure-sensitive adhesive composition of Example 1, except that the conditions for preparing the pressure-sensitive adhesive composition were changed to those shown in Table 1.

[0134] <Production of adhesive sheets> An adhesive sheet 6 was obtained in the same manner as in the production of the adhesive sheet in Example 1, except that, instead of adhesive composition 1, adhesive composition 6 was applied to a thickness of 150 μm.

[0135] <Preparation of Laminate> A laminate was obtained in the same manner as in Example 1, except that adhesive sheet 1 was changed to adhesive sheet 6 and adherend A was changed to a polycarbonate plate having a thickness of 1 mm (Teijin's "PC1151").

[0136] Example 7 <Production of (meth)acrylic polymer> A syrup of a (meth)acrylic polymer was obtained as a base component in the same manner as in the production of a (meth)acrylic polymer in Example 1, except that the base component composition was changed to the conditions shown in Table 1.

[0137] <Production of Pressure-Sensitive Adhesive Composition> Pressure-sensitive adhesive composition 7 was obtained in the same manner as in the production of the pressure-sensitive adhesive composition of Example 1, except that the conditions for preparing the pressure-sensitive adhesive composition were changed to those shown in Table 1.

[0138] <Production of adhesive sheets> Adhesive sheet 7 was obtained in the same manner as in the production of the adhesive sheet in Example 1, except that, instead of adhesive composition 1, adhesive composition 7 was applied to a thickness of 50 μm, and the 75 μm thick polyester film (release sheet) coated with a silicone release agent was changed to a 50 μm thick polyester film (release sheet) coated with a silicone release agent.

[0139] <Preparation of Laminate> A laminate was obtained in the same manner as in Example 1, except that adhesive sheet 1 was changed to adhesive sheet 7 and adherend A was changed to a polycarbonate plate having a thickness of 2 mm (Mitsubishi Gas Chemical Company, MRS58TB).

[0140] Comparative Example 1 <Production of (meth)acrylic polymer> A syrup of a (meth)acrylic polymer was obtained as a base component in the same manner as in the production of a (meth)acrylic polymer in Example 1, except that the base component composition was changed to the conditions shown in Table 1.

[0141] <Production of Pressure-Sensitive Adhesive Composition> An adhesive composition 1a was obtained in the same manner as in the production of the adhesive composition of Example 1, except that the preparation conditions for the adhesive composition were changed to those shown in Table 1.

[0142] <Production of adhesive sheets> An adhesive sheet 1a was obtained in the same manner as in the production of the adhesive sheet in Example 1, except that adhesive composition 1a was applied in place of adhesive composition 1 so as to give a thickness of 250 μm.

[0143] <Preparation of Laminate> A laminate was obtained in the same manner as in the preparation of the laminate in Example 1, except that the adhesive sheet 1 was changed to the adhesive sheet 1a.

[0144] Comparative Example 2 <Production of (meth)acrylic polymer> A syrup of a (meth)acrylic polymer was obtained as a base component in the same manner as in the production of a (meth)acrylic polymer in Example 1, except that the base component composition was changed to the conditions shown in Table 1.

[0145] <Production of Pressure-Sensitive Adhesive Composition> An adhesive composition 2a was obtained in the same manner as in the production of the adhesive composition of Example 1, except that the preparation conditions of the adhesive composition were changed to those shown in Table 1.

[0146] <Production of adhesive sheets> An adhesive sheet 2a was obtained in the same manner as in the production of the adhesive sheet in Example 1, except that the adhesive composition 2a obtained was used instead of the adhesive composition 1.

[0147] <Preparation of Laminate> A laminate was obtained in the same manner as in Example 1, except that the adhesive sheet 1 was changed to the adhesive sheet 2a and the adherend B was changed to a polyethylene terephthalate film having a thickness of 0.1 mm ("A4360" manufactured by Toyobo Co., Ltd.) In producing this laminate, the polyethylene terephthalate film and the adhesive sheet (adhesive layer) were attached together so that the adhesive surface of the polyethylene terephthalate film was in contact with the adhesive sheet (adhesive layer).

[0148] Comparative Example 3 <Production of (meth)acrylic polymer> A syrup of a (meth)acrylic polymer was obtained as a base component in the same manner as in the production of a (meth)acrylic polymer in Example 1, except that the base component composition was changed to the conditions shown in Table 1.

[0149] <Production of Pressure-Sensitive Adhesive Composition> An adhesive composition 3a was obtained in the same manner as in the production of the adhesive composition of Example 1, except that the preparation conditions of the adhesive composition were changed to those shown in Table 1.

[0150] <Production of adhesive sheets> An adhesive sheet 3a was obtained in the same manner as in the production of the adhesive sheet in Example 1, except that adhesive composition 3a was applied in place of adhesive composition 1 so as to give a thickness of 175 μm.

[0151] <Preparation of Laminate> A laminate was obtained in the same manner as in the preparation of the laminate in Example 1, except that the adhesive sheet 1 was changed to adhesive sheet 3a and the adherend A was changed to a polycarbonate plate having a thickness of 3 mm.

[0152] Evaluation method (Tg of tackifier) A Hitachi High-Tech Science DSC600 was used to measure the glass transition temperature of the tackifier. 5 mg of alumina was used as a reference, and about 5 mg of the tackifier resin with the solvent removed was placed in a 5 mm diameter aluminum sample pan, and the temperature was raised from 0°C to 150°C at a heating rate of 10°C / min in an environment with a nitrogen flow rate of 50 ml / min. The inflection point at which the specific heat changed was read as the glass transition temperature of the tackifier resin.

[0153] (Gel fraction) Approximately 0.1 g of the adhesive sheet (adhesive layer) was placed in a sample bottle, 30 ml of ethyl acetate was added, and the mixture was shaken for 24 hours. The contents of the sample bottle were then filtered through a 200-mesh stainless steel wire screen, and the residue on the screen was dried at 120°C for 1 hour to measure the dry mass (g). The obtained dry mass was calculated using the following formula: Gel fraction (mass%) = (dry mass / collected mass of adhesive sheet) × 100 Equation 1 The gel fraction was calculated using the method described in (1).

[0154] <Residual stress after 60 seconds> First, a laminated sheet having a thickness of 1000 μm was prepared by laminating a plurality of pressure-sensitive adhesive layers formed from each pressure-sensitive adhesive composition. The laminated sheet was then pressurized in an autoclave under an atmosphere of 30° C. and 0.5 MPa for 10 minutes to obtain a measurement sample. The obtained measurement sample was subjected to a probe diameter of 8 mm and an initial heating temperature of 105° C. for 2 minutes, and then a 15% torsional strain was applied to the obtained measurement sample while maintaining the temperature at 105° C., and the shear stress was read 1 minute after the load. This shear stress was taken as the residual stress of the pressure-sensitive adhesive layer after 60 seconds. The residual stress after 60 seconds means the residual stress after 60 seconds after applying a 15% torsional shear stress at 105° C.

[0155] <Measurement of the elasticity of the adherend> Hitachi High-Tech Science's TMA7100 was used to measure the expansion and contraction rates of adherend A and adherend B. The adherends were placed in an environment with a nitrogen flow rate of 200 ml / min, and the temperature was raised from 23°C to 150°C at a heating rate of 20°C / min. The expansion and contraction rates were read when the sample temperature reached 110°C, and these were taken as the expansion and contraction rates (X1 and X2) of the adherends. For adherends with a thickness of more than 1 mm, a sample side of 1 cm square was prepared and measured in compression mode, and for films, the sample was cut to 5 mm x 40 mm and then measured in tension mode.

[0156] <High-temperature / low-temperature cycle test> The laminates prepared in the examples and comparative examples were placed in a thermal shock tester ES-57L manufactured by Hitachi Air Conditioning SE. The temperature of the atmosphere in the test chamber was changed from -20°C to 85°C, and then changed back to -20°C, which constituted one cycle, and the temperature was repeatedly changed. The time per cycle was set to 1 hour, and the test was terminated after 72 hours had elapsed. The laminates after the test were visually inspected and evaluated according to the following criteria. ≪Judgment criteria≫ ◯: Peeling from the edge was less than 2 mm, and no air bubbles or the like were generated. Peeling was extremely easily suppressed even when temperature changes occurred. Δ: Peeling from the edge was 2 mm or more and less than 5 mm, no air bubbles were generated, and peeling was easily suppressed even when temperature changes occurred. ×: Peeling from the edge was 5 mm or more or air bubbles were observed, and peeling was likely to occur due to temperature changes.

[0157] <Boiling test> The laminates produced in the Examples and Comparative Examples were placed in a boiling water bath and held in this state for 2 hours, after which the laminates were taken out and visually inspected and evaluated according to the following criteria. ◯: Peeling from the edge was less than 2 mm, and no air bubbles or the like were generated. Peeling between the adherend and the pressure-sensitive adhesive sheet was extremely unlikely to occur even in a high-temperature environment. Δ: Peeling from the edge was 2 mm or more and less than 5 mm, no air bubbles were generated, and peeling between the adherend and the pressure-sensitive adhesive sheet was unlikely to occur even in a high-temperature environment. ×: Peeling from the edge was 5 mm or more or air bubbles were observed, and peeling was likely to occur in a high temperature environment.

[0158] Evaluation results Table 1 shows the (meth)acrylic polymer composition and pressure-sensitive adhesive composition preparation conditions used in producing the pressure-sensitive adhesive sheets obtained in each of the Examples and Comparative Examples, as well as the measurement results of the thickness, gel fraction, and 60-second residual stress (residual stress 60 seconds after application of a 15% torsional shear stress at 105°C) of the resulting pressure-sensitive adhesive sheets.

[0159] Table 1 also shows the evaluation results (results of high-temperature-low-temperature cycle test and boiling test) of laminates obtained using the pressure-sensitive adhesive sheets obtained in each Example and Comparative Example and the adherends A and B. Table 1 also shows the expansion / contraction ratios (2%) and thicknesses of adherends A and B when heated from 23°C to 110°C, as well as the value of |(X1-X2)| in formula (1). X1 indicates the expansion / contraction ratio (%) of adherend A when heated from 23°C to 110°C, and X2 indicates the expansion / contraction ratio (%) of adherend B when heated from 23°C to 110°C.

[0160] In addition, in the preparation conditions of the pressure-sensitive adhesive composition in Table 1, a blank cell means that the corresponding raw material was not used.

[0161] As can be seen from Table 1, the adhesive sheets obtained in the examples were resistant to peeling even when adherends with different stretch rates were bonded together, and the adhesive sheets had good adhesion to the adherends even when placed in a high-temperature environment, and peeling of the adhesive sheet was resistant, with peeling at the edges being particularly easily suppressed. Thus, it was demonstrated that an adhesive sheet that is resistant to peeling even when exposed to temperature changes and high-temperature environments can be obtained by providing the adhesive layer obtained from the adhesive composition containing at least a (meth)acrylic polymer and a silane coupling agent, and by having the gel fraction and residual stress after 60 seconds within the specified ranges of the adhesive layer.

[0162] [Table 1]

Claims

1. A pressure-sensitive adhesive sheet used to bond a pair of adherends having different stretch rates, A pressure-sensitive adhesive layer is provided from the pressure-sensitive adhesive composition, The pressure-sensitive adhesive composition contains at least a base agent containing a (meth)acrylic polymer and a silane coupling agent, The pressure-sensitive adhesive layer has a gel fraction of 80% or more, the pressure-sensitive adhesive layer has a residual stress of 3.0 kPa or more and 10.0 kPa or less 60 seconds after application of a 15% torsional shear stress at 105°C; The following formula (1) |(X1-X2)|≧0.1%...(1) (Here, when one of the pair of adherends is adherend A and the other is adherend B, X1 is the expansion / contraction rate (%) when adherend A is heated from 23° C. to 110° C., and X2 is the expansion / contraction rate (%) when adherend B is heated from 23° C. to 110° C.) Meet the adhesive sheet.

2. The pressure-sensitive adhesive sheet according to claim 1 , wherein the pressure-sensitive adhesive composition comprises a monofunctional monomer having a ring structure.

3. The pressure-sensitive adhesive sheet according to claim 1 , wherein the pressure-sensitive adhesive composition contains 0.05 parts by mass or more and 5 parts by mass or less of the silane coupling agent relative to 100 parts by mass of the base agent.

4. The pressure-sensitive adhesive composition is a solvent-free type, The pressure-sensitive adhesive sheet according to claim 1 , wherein the pressure-sensitive adhesive layer has a crosslinked structure formed by a polyfunctional monomer.

5. The pressure-sensitive adhesive sheet according to claim 1 , wherein the pressure-sensitive adhesive composition comprises an acrylic tackifier.

6. The pressure-sensitive adhesive sheet according to claim 1 or 2, which has a thickness of 75 μm or more.

7. The pressure-sensitive adhesive sheet according to claim 1 or 2, wherein the adherend having a higher stretch rate out of the adherend A and the adherend B has a thickness of 2 mm or more.

8. The pressure-sensitive adhesive sheet according to claim 1 or 2, wherein the adherend A and the adherend B each have a total light transmittance of 50% or more.

9. The pressure-sensitive adhesive sheet according to claim 8, which is for use in car windows, building windows or door windows.

10. A laminate comprising the pressure-sensitive adhesive sheet according to claim 1 or 2 and a pair of adherends having mutually different stretch rates.

Citation Information

Patent Citations

  • Acrylic pressure-sensitive adhesive tape

    JP2013159704A

  • Optically transparent adhesive, method of use thereof, and articles using the same.

    JP2014510807A

  • Laminate having adhesive layer and method for producing laminate

    JP2019111660A

  • Pressure sensitive adhesive sheet with release film and manufacturing method thereof

    JP2019112505A

  • Adhesive composition and adhesive sheet

    JP2021113280A